Kajian Kelayakan Ekonomi Jalan Lingkar Kertek Wonosobo Jawa Tengah - Usmany, Ayu Pranedya; Santosa, Wimpy (Universitas Kristen Maranatha, 2024)
The topography of Wonosobo District affects the geometric condition of roads in areas of the district. Some areas in Wonosobo Regency are hills and mountains, so there is a downhill road for ± 9 km. This road connects Parakan Sub-district in Temanggung Regency with Kertek Sub-district in Wonosobo Regency. This route is prone to traffic accidents, resulting in many casualties and material casualties. This study was conducted based on the economic benefit value of the new road construction. The Benefit Cost Ratio and Net Present Value analyses were conducted by considering vehicle operating costs, time value, and reduction in traffic accidents. The analysis results show that in scenario I, the savings in vehicle operating costs are Rp 1,439,473,846,994, and in scenario II, Rp 1,524,871,315,937. In scenario I, the benefit cost ratio value is 1.66 with an NPV of Rp 385,588,148,902, and in scenario II, it is 1.68 with a net present value of Rp 395,171,651,336. The economic feasibility analysis results show that the Kertek Wonosobo Ring Road is viable to build.